2011
DOI: 10.1001/archophthalmol.2011.289
|View full text |Cite
|
Sign up to set email alerts
|

Postenucleation Adjuvant Chemotherapy With Vincristine, Etoposide, and Carboplatin for the Treatment of High-Risk Retinoblastoma

Abstract: Background: Analysis of 52 eyes with high-risk retinoblastoma managed with postenucleation adjuvant chemotherapy using vincristine sulfate, etoposide phosphate, and carboplatin showed no evidence of systemic metastasis in any case during a mean (range) follow-up of 66 (12-202) months.Purpose: To determine the efficacy of postenucleation adjuvant chemotherapy with vincristine, etoposide, and carboplatin in the prevention of metastasis for patients with high-risk retinoblastoma.Methods: Retrospective, nonrandomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 32 publications
0
82
0
4
Order By: Relevance
“…14,15 In our study, 7 cases (5%) with high-risk retinoblastoma developed systemic metastasis during a mean follow-up of 37 months. Of these 7 cases, 5 (3%) developed systemic metastasis despite receiving adjuvant treatment.…”
Section: Kaliki Et Al High-risk Retinoblastomamentioning
confidence: 54%
“…14,15 In our study, 7 cases (5%) with high-risk retinoblastoma developed systemic metastasis during a mean follow-up of 37 months. Of these 7 cases, 5 (3%) developed systemic metastasis despite receiving adjuvant treatment.…”
Section: Kaliki Et Al High-risk Retinoblastomamentioning
confidence: 54%
“…In such cases, systemic intravenous chemotherapy (chemoreduction) might be preferable. 18 In summary, our analysis has shown that eyes with retinoblastoma and partial or total retinal detachment can be successfully treated with IAC in many cases, and most eyes can be salvaged, avoiding enucleation. Some of these eyes can regain visual acuity.…”
Section: Discussionmentioning
confidence: 74%
“…The chemotherapy protocol for IVC is similar to that used for prevention of metastasis in high-risk retinoblastoma. 38 Unfortunately, IVC alone might not completely control advanced retinoblastoma because group D eyes show 53% local intraocular recurrence and group E eyes show 75% local recurrence, necessitating EBRT, IAC, or enucleation. 26,32 In one analysis, globe salvage was achieved using IVC followed by IAC in 67% of group D eyes and 63% of group E eyes 33 (Figures 2 and 3).…”
Section: Saving Advanced Group D or E Eyesmentioning
confidence: 99%